Determining Basic Cost of Electricity on the Regionalization System - Yusra Sabri; Hermagasantos Zein (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In electric business, costs that support production called with allowable electric cost or basic cost of electricity. Therefore, the basic cost of electricity has to get more attention seriously from the electric company in order to be trusted by consumers. In determining of the costs must be transparence and do the optimizing in calculating process because of revenues from customers have to be able to cover the basic cost of electricity so that the electric company does not go bankrupt. This paper will create concept and formulations for determining the basic cost of electricity in a region. There are a few different characteristics of each region will influence the costs. The basic cost of electricity can be different among regions that were caused by generating, investment and losses in the region. Later has been done a numerical simulation to simple power system and the results are matching with desired expectations.